Excise Tax Thank You Letters - PAUL JOHNSON (Tufts Archival Research Center, 2007)
Missing Attachments; Memo from Paul Johnson to Fred Panzer regarding letters thanking Congress members for voting against excise taxes. Includes letter to Sen. Dole thanking him for his support and urging him to continue fighting excise taxes. Attached to Tobacco Institute schedule of expenses, July 1986.